Controlling Excitation Inversion of a Cooper Pair Box Interacting with a Nanomechanical Resonator - Valverde, C. [UNESP]; de Oliveira, H. C. B.; Avelar, A. T.; Baseia, B. (Iop Publishing Ltd, 2012)
We investigate the action of time-dependent detunings upon the excitation inversion of a Cooper pair box interacting with a nanomechanical resonator. The method employs the Jaynes-Cummings model with damping, assuming different decay rates of the Cooper pair box and various fixed and time-dependent detunings. It is shown that, when the presence of damping plus constant detunings destroys the collapse/revival effects, convenient choices of time-dependent detunings allow one to reconstruct such events in a perfect way. It is also shown that the mean excitation of the nanomechanical resonator is more robust against damping of the Cooper pair box for convenient values of time-dependent detunings.